Web of Science‐Based Visualization of Metabolic Dysfunction‐Associated Fatty Liver Disease in Pediatric and Adolescent Populations: A Bibliometric Study - Liangyu Hu; Huarong Du; QianQian Zhou; Chunlei Liu; Tiansong Zhang; Min Yuan (Health Science Reports)
ABSTRACT Background and Aims The prevalence of metabolism‐associated fatty liver disease (MAFLD) in children is on the rise. This study employs visualization and analysis to evaluate the research implications, current advancements, and emerging trends in pediatric MAFLD, with the aim of elucidating its pathogenesis and informing the development of clinical treatment strategies. Methods Using visualization software, we conducted a visual analysis and mapping of the journal distribution, leading institutions, prominent authors, annual publication trends, and keyword frequencies among the 1179 scholarly articles retrieved from the Web of Science Core Collection for this study. Results The overall publication volume demonstrated an upward trend, with a total of 200 journals, contributions from 63 countries, 882 research institutions, and 5605 authors involved, including 84 who were identified as core authors. The main research team is led by Nobili, Valerio. The main research institutions are concentrated in Italy, the United States, and China. A total of 473 keywords were included, and the keywords with high frequency and medium centricity are insulin resistance, metabolic syndrome, children, steatohepatitis, adolescents, hepatic steatosis, nash, obesity, diagnosis, and fibrosis, which resulted in six keyword clusters. Conclusion MAFLD represents a significant public health concern. Research on children and adolescents with MAFLD continues to attract high interest. Noninvasive diagnostic methods, pathogenesis (intestinal microbiota research), disease prediction (gene research) are current research hotspots.